Regulation of hydrogen rich water on strawberry seedlings and root endophytic bacteria under salt stress - Wang, Renyuan; Yang, Xijia; Chi, Yaowei; Zhang, Xia; Ma, Xianzhong; Zhang, Dan; Zhao, Ting; Ren, Yongfeng; Yang, Haiyan; Ding, Wenjiang; Chu, Shaohua; Zhou, Pei (Frontiers in Plant Science, 2024)
Salt stress could lead to plant growth barriers and crop yield reduction. Strawberries are sensitive to salt stress, and improving salt tolerance is important for strawberry production. This study aimed to explore the potential of hydrogen-rich water (HRW) to enhance salt tolerance in strawberries. Through pot experiments, we investigated how HRW affects plant growth, ion absorption, osmotic stress, oxidative stress, antioxidant enzyme levels, hormone levels, and root endophytic bacteria in strawberry seedlings under salt stress. The results showed that under 100 mM NaCl treatment, 50% and 100% HRW treatments significantly increased strawberry biomass by 0.29 g and 0.54g, respectively, wherein, 100% HRW significantly increased the shoot and root length by 15.34 % and 24.49 %, respectively. In addition, under salt stress the absorption of K+ by strawberry seedlings was increased with the HRW supplement, while the absorption of Na+ was reduced. Meanwhile, HRW treatment reduced the transfer of Na+ from root to shoot. Furthermore, under salt stress, HRW treatment increased the relative water content (RWC) by 12.35%, decreased the electrolyte leakage rate (EL) by 7.56%. HRW modulated phytohormone levels in strawberry seedlings, thereby alleviating the salt stress on strawberries. Moreover, HRW was found to promote plant growth by altering the diversity of bacteria in strawberry roots and recruiting specific microorganisms, such as Tistella. Our findings indicate that HRW could help restore the microecological homeostasis of strawberry seedlings, thus further mitigating salt stress. This study provides a novel perspective on the mechanisms by which HRW alleviates salt stress, thereby enriching the scientific understanding of hydrogen’s applications in agriculture.